2005
DOI: 10.1007/s00425-005-0017-y
|View full text |Cite
|
Sign up to set email alerts
|

Isogene specific oligo arrays reveal multifaceted changes in gene expression during grape berry (Vitis vinifera L.) development

Abstract: The transition from a green, hard, and acidic pericarp to a sweet, soft, coloured, and sugar-rich ripe fruit occurs in many unrelated fruit species. High throughput identification of differentially expressed genes in grape berry has been achieved by the use of 50-mers oligoarrays bearing a set of 3,200 Unigenes from Vitis vinifera to compare berry transcriptome at nine developmental stages. Analysis of transcript profiles revealed that most activations were triggered simultaneously with softening, occurring wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
222
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(255 citation statements)
references
References 76 publications
29
222
2
2
Order By: Relevance
“…In the past, it was proposed that glycolysis was inhibited after véraison (Famiani et al 2000). Then, through some microarray analyses, it was reported that some glycolytic enzymes were up regulated during ripening (da Silva et al 2005;Terrier et al 2005). In the present work, we observed that among the characterized spots, there are some enzymes relative to glycolysis and Krebs cycle, indicating that also in Pinot skins, primary metabolism undergoes some modulations during ripening.…”
Section: General Metabolismsupporting
confidence: 55%
See 2 more Smart Citations
“…In the past, it was proposed that glycolysis was inhibited after véraison (Famiani et al 2000). Then, through some microarray analyses, it was reported that some glycolytic enzymes were up regulated during ripening (da Silva et al 2005;Terrier et al 2005). In the present work, we observed that among the characterized spots, there are some enzymes relative to glycolysis and Krebs cycle, indicating that also in Pinot skins, primary metabolism undergoes some modulations during ripening.…”
Section: General Metabolismsupporting
confidence: 55%
“…As reported in many papers, grape ripening affects the expression of many enzymes involved in metabolic pathways of the primary metabolism such as those related to glycolysis/gluconeogenesis, pentose-phosphate pathway and Krebs cycle (Giribaldi et al 2007;Negri et al 2008a;Robinson et al 1997;Pilati et al 2007;Ruffner and Hawker 1977;Famiani et al 2000;da Silva et al 2005;Terrier et al 2005). In the past, it was proposed that glycolysis was inhibited after véraison (Famiani et al 2000).…”
Section: General Metabolismmentioning
confidence: 96%
See 1 more Smart Citation
“…The genomic information has significantly increased in the last 10 years, from expressed sequence tag (EST) sequencing programs (Iandolino et al 2004) to the release of the Pinot noir genome sequence and annotation (Jaillon et al 2007). Several generations of microarrays have been created and used, from the first 3,500 unigene Qiagen/Operon chips (Terrier et al 2005) to the newly developed genomewide slides bearing up to 30,000 unigenes (Bellin et al 2009). Most recently, the grapevine research community gained access to massive parallel signature sequencing-based transcriptome analysis, the so-called deep RNA sequencing approach (Zenoni et al 2010).…”
mentioning
confidence: 99%
“…ADH plays a central role in stress-response and could be a fruit-ripening related marker on grapevine. The up-regulation of some ADH genes for fruit-ripening implies that ethanol fermentation is a normal development response in grapes (Sarni-Manchado et al, 1997;Sweetman et al, 2009;Terrier et al, 2005). And Tesniere et al (2009) found that over-expression or down-regulation of VvADH resulted in unexpected responses at the primary and secondary metabolism levels in leaves and berries.…”
Section: Discussionmentioning
confidence: 99%